2014
DOI: 10.1109/tsg.2013.2274525
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Electricity Cost Minimization Through Energy Buffering in Data Centers

Abstract: More and more cloud computing services are handled by different Internet operators in distributed Internet data centers (IDCs), which incurs massive electricity costs. Today, the power usage of data centers contributes to more than 1.5% market share of electricity consumption across the United States. Minimization of these costs benefits cloud computing operators, and attracts increasing attentions from many research groups and industrial sectors. Along with the deployment of smart grid, the electrical real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Recently, the relevant literature has indicated that there also is increasing interest in the optimal operation of data centres [12, 13, 17–23]. The models proposed in the technical literature are related mainly to the control of only the data centre's energy consumption in order to improve efficiency and to give them the potential for participating in a demand‐response program [1923]. In [19], the benefits of integrating data centres into demand‐response schemes were discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the relevant literature has indicated that there also is increasing interest in the optimal operation of data centres [12, 13, 17–23]. The models proposed in the technical literature are related mainly to the control of only the data centre's energy consumption in order to improve efficiency and to give them the potential for participating in a demand‐response program [1923]. In [19], the benefits of integrating data centres into demand‐response schemes were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In [22], a load‐control method for data centres was presented that was based on both the data network and the electrical network with the aim of controlling power usage associated with participation in the demand‐response program. In [23], an approach was proposed to enable electrical energy buffering in batteries to predictably minimise data centres’ electricity costs in smart grids. In this approach, the batteries are charged when the price of electricity is low, and they are discharged to power servers when the price of electricity is high.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, a new approach regarding electricity cost reduction problem presents the internet payload requests and SG dynamic electricity pricing mechanism [27]. This approach also discusses the predictive cost control for the smart charging on both sides: (1) battery energy for the servers and (2) electricity from the power grid.…”
Section: Methodologies Regarding Fog Based Architecturementioning
confidence: 99%
“…This is due to two reasons. One is manual faults like improper scheduling and work overload [5,10] and other is due to hike in monetary cost of electricity [13]. The manual faults can be resolved by using monitoring and virtualization [12].…”
Section: Energy Consumption Problemmentioning
confidence: 99%